2005
DOI: 10.1007/s00170-004-2203-7
|View full text |Cite
|
Sign up to set email alerts
|

Parametric optimisation of wire electrical discharge machining of γ titanium aluminide alloy through an artificial neural network model

Abstract: In the present research, wire electrical discharge machining (WEDM) of γ titanium aluminide is studied. Selection of optimum machining parameter combinations for obtaining higher cutting efficiency and accuracy is a challenging task in WEDM due to the presence of a large number of process variables and complicated stochastic process mechanisms. In general, no perfect combination exists that can simultaneously result in both the best cutting speed and the best surface finish quality. This paper presents an atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 18 publications
0
46
0
1
Order By: Relevance
“…Shah et al (2010) have shown that the material thickness has little effect on the material removal rate and kerf but is a significant factor in terms of surface roughness in wire electrical discharge machining (WEDM) of tungsten carbide samples. Now-a-days, artificial neural network is used as a tool in modeling of EDM process (Spedding and Wang 1997;Tsai and Wang 2001;Sarkar et al 2006;Mandal et al 2007;Assarzadeh and Ghoreishi 2008).…”
Section: Review Of Roughness Study In Machiningmentioning
confidence: 99%
“…Shah et al (2010) have shown that the material thickness has little effect on the material removal rate and kerf but is a significant factor in terms of surface roughness in wire electrical discharge machining (WEDM) of tungsten carbide samples. Now-a-days, artificial neural network is used as a tool in modeling of EDM process (Spedding and Wang 1997;Tsai and Wang 2001;Sarkar et al 2006;Mandal et al 2007;Assarzadeh and Ghoreishi 2008).…”
Section: Review Of Roughness Study In Machiningmentioning
confidence: 99%
“…Test result reveals that in machining Al 2 O 3p /6061Al composites a very low wire tension, a high flushing rate and a high wire speed are required to prevent wire breakage: an appropriate servo voltage, a short pulse-on time, and a short pulse-off time, which are normally associated with a high current speed, have a little effect on the surface roughness. Sarkar et al (2006) studied the WEDM of γ titanium aluminide. They also attempted to develop an appropriate machining strategy for a maximum process yield criteria.…”
Section: Past Research Work On Wedm Of Mmcsmentioning
confidence: 99%
“…They coupled a genetic algorithm (GA) with an ANN to forecast the surface roughness. S. Sarkar et al 29 produced a multilayer feed-forward-ANN model to predict the process parameters of the machining of g titanium aluminide with a wire-electrical-discharge machine. A. K. Singh et al 30 used a multilayer feed-forward ANN to predict the flank wear of high-speed steel drill bits for drilling holes into a copper workpiece.…”
Section: Introductionmentioning
confidence: 99%